'Real Ale' Enthusiasts, Serious Leisure and the Costs of Getting 'Too Serious' About Beer. (1st January 2016) - Thurnell-Read, Thomas
Abstract : The article uses the concept of serious leisure to explain the leisure commitments made by members of the British consumer campaign group the Campaign for Real Ale (CAMRA) and that of Real Ale enthusiasts in general. Drawing on in-depth qualitative research including interviews with CAMRA branch members and staff, the article demonstrates that beer appreciation can be understood as a serious rather than a casual leisure activity. While many of the benefits to participation typical of serious leisure activities are identified, so are the numerous "costs" involved. Beyond costs relating to money, time, obligation, and organizational conflicts, the article suggests that Real Ale enthusiasts are at times marginalized by wider cultural stereotypes positioning them as obsessive and snobbish. The article concludes with discussion of how the concept of the cultural omnivore might explain how serious leisure practitioners are often marginalized because of their specialism in a single field rather than many.